Potensi dan Tantangan Ekonomi Bonsai di Desa Ranugedang: Studi Kasus Pada Usaha Bonsai Di Krajan - Purwantoro, Farich; M Imam (Kalam Nusantara Institute, 2025)
king this article is to complete the work of the PKM which uses the ABCD method by developing resources in the village that we can further develop and it can also inform the people in Liprak Wetan village that Moringa leaves can also be processed and later the processed results will not only provide benefits for himself and his family can also make money. Indonesia is a country that is rich in spices and vegetables that have been cultivated since ancient times. With so many vegetables and spices, many people use them to make traditional herbal medicine, herbal teas, and other foods that are rich in benefits. We are KKN students whose job is to make a product. It is also not difficult to find what ingredients will be processed in such a way but are rich in benefits. herbal tea with very abundant benefits. However, in our country the processing of Moringa leaves has not spread widely, even in our own country, the processing of Moringa leaves is also still minimal, people know about the abundance of benefits. So far, Moringa leaves are only consumed as vegetables by the public. Indonesia.